Optimal cut-off points for waist circumference in the definition of metabolic syndrome in Chile. Issue 16 (3rd November 2020) - Petermann-Rocha, Fanny; Martínez-Sanguinetti, María Adela; Ho, Frederick K; Celis-Morales, Carlos; Pizarro, Alonso
Abstract: Objective: To identify sex-specific cut-off points for waist circumference (WC) in the definition of metabolic syndrome (MetS) for the Chilean adult population. Design: MetS was defined as the presence of at least two out of four of the following criteria: TAG ≥1·7 mmol/l; HDL-cholesterol: <1·3 mmol/l in women and <1·0 mmol/l in men; systolic blood pressure ≥130 mmHg and/or diastolic blood pressure ≥85 mmHg; and fasting glucose ≥ 5·6 mmol/l or current treatment for diabetes. The receiver operating characteristics curve and the AUC were computed to derive the specificity and sensitivity using bootstrapping (10 000 iterations restricted to have at least between 40 and 60 % of the original population). The optimal cut-off point for the Chilean population was computed by sex. Setting: A representative sample of the Chilean population aged ≥15 years. Participants: 8182 participants (60 % women) from the three available Chilean National Health Surveys conducted in 2003, 2009–2010 and 2016–2017. Results: WC had a good predictive ability for MetS (AUC for men 0·74 (95 % CI 0·72, 0·76); AUC for women 0·71 (95 % CI 0·68, 0·73)). The optimal cut-off points for WC, in the definition of MetS, were 92·3 cm (95 % CI 90·5, 94·4) and 87·6 cm (95 % CI 85·8, 92·1) for men and women, respectively. Conclusions: The mentioned cut-off points should be used for WC in the definition of MetS in Chile. As a result, the current recommendation (WHO/International Diabetes Federation) for WC, in the identification of MetS, is not supported by these findings in a representative sample of the Chilean adult population.